Exploration of Attentional and Executive Abilities in French-Speaking Children Immersed in Dutch Since 1, 2, 3, and 6 Years - Gillet, Sophie; Barbu, Cristina Anca; Poncelet, Martine (Frontiers in Psychology, 2020)
Advantages in diverse aspects of cognitive functioning have been reported in early bilinguals as well as in children frequenting an early bilingual immersion school program. However, during the last decade, some studies failed to replicate these advantages. Currently, the presence of cognitive benefits in children frequenting an immersion program remains debated. The lack of consistency between the studies investigating this question could stem from the variability of immersion programs attended, the time spent in immersion, the diversity of tasks used to evaluate cognitive functioning, or the control of major confounding factors in the matching of the immersed and non-immersed groups. To control these different variables, we compared 196 Dutch immersed and 195 non-immersed French-speaking children, at different moments of the primary schooling (grades 1, 2, 3, and 6) by using the same attentional and executive tasks as those used in studies having shown a bilingual advantage. Furthermore, these groups were matched on socioeconomic status (SES), verbal and nonverbal reasoning, and sport, music, and video game practice. In first, second, and third grades, performances of immersed and matched non-immersed children do not differ for any task. However, in sixth grade, immersed children outperformed non-immersed children on the cognitive flexibility task as well as on an additional task evaluating working memory. These results suggest that, in French-speaking children immersed in Dutch, cognitive advantages could emerge at the end of primary immersion schooling. We conclude that the emergence of cognitive advantages may vary depending on the characteristics of the second language learned, as previous studies conducted in English immersion using the same tasks and evaluating a similar CLIL context showed that the advantages appear earlier in the primary schooling but are absent at the end of it.